Adolescent selfie: an Italian Society of Paediatrics survey of the lifestyle of teenagers - Martina Smorti; Annarita Milone; José Gonzalez Gonzalez; Giovanni Vitali Rosati (BMC, 2019)
Abstract Background Epidemiological studies worldwide indicate that teenagers are at risk of internalizing and externalizing problems that persist into adulthood. In our country, there are few epidemiological studies on adolescents internalizing and externalizing problems. These studies, however, were not conducted in all of Italy. The aim of this study, promoted by the Italian Society of Paediatrician (SIP), was to investigate: a) the lifestyle and the prevalence of internalizing and externalizing problems in Italian teenagers and b) the risk and protective factors in family and social contexts. A further aim was to analyse gender differences in the above-mentioned variables. Methods 11,527 adolescents aged 13 to 21 years were recruited among students of Italian high schools. Participants were contacted by school authorities inviting them to participate in an internet survey on youth health and lifestyle. If they agreed to participate, the adolescents filled out an on-line anonymous questionnaire. The questionnaire was composed of 60 multiple choice items to investigate nutrition, body perception and lifestyle, internet exposure and sexual behaviour, externalizing and internalizing problems, family context and social context. Participation in the study was completely voluntary. The statistical significance of gender differences was tested by means of Chi-square analyses. Results displayed that Italian female adolescents are at risk of internalizing problems while males are at higher risk of externalizing problems. Moreover, several risk factors emerged from the family context in terms of violence, physical and psychological abuse. Conclusions It is critical to make paediatricians and schools aware of the main points to improve prevention and healthcare in the teenage population. To our knowledge, this is the first study in the Italian context to enrol more than 11,000 adolescents.